THE USE OF DRAW IO AS DIGITAL MIND MAP TO IMPROVE STUDENTS' CREATIVITY AND STUDENTS' CONCEPT MASTERY IN LEARNING HUMAN INFLUENCE ON ECOSYSTEM - Mohamad Yusril Aldiana Mahendra, - (2021)
ABSTRACT The Covid-19 pandemic has significantly affected the education system worldwide. During this pandemic, teachers have a challenge to improve students' concept mastery and students' creativity through online learning. This research aims to determine the application of Draw IO as digital mind map to improve students' concept mastery and students' creativity. Draw IO is a diagram tools that is the most flexible in making flowchart process diagrams especially for mind mapping. This research using pre-experimental method with one group pre-test and post-test design in one of the private schools in Bandung Barat which use Cambridge Curricullum. There were 29 students of secondary 3 level who are participated on this research. Creativity was measured on four aspect which are fluency, flexibility, originality, and ellaboration. The result showed that most of the students still on moderate level which means that the creativity shows good enough quality. Meanwhile, the result about students' concept mastery was measured by cognitive test were showed the improvement with N-gain is 0.42 and categorized as medium improvement. The siginificancy value on the hypothesis test is less than 0.05. It indicates there are significant different in students' concept mastery on learning human influence on ecosystems by using Draw IO as digital mind map. Based on the result, Draw IO can be used as learning tools for improving students' concept mastery and students' creativity. Keyword: Draw.IO as Digital Mind Map, Students' Concept Mastery, Students' Creativity , and Human Influnce on Ecosystems ABSTRAK Pandemi Covid-19 telah secara signifikan memengaruhi sistem pendidikan di seluruh dunia. Selama pandemi ini, pengajar mendapat tantangan untuk meningkatkan penguasaan konsep dan kreativitas siswa melalui pembelajaran online. Penelitian ini bertujuan untuk mengetahui penerapan Draw IO sebagai mind map digital untuk meningkatkan penguasaan konsep dan kreativitas siswa. Draw IO adalah media yang paling fleksibel dalam membuat diagram terkhusus dalam pembuatan mind map. Penelitian ini menggunakan metode pre -ekperimen dengan one group pre-test dan post-test desain yang dilakukan di salah satu sekolah swasta di Bandung Barat yang menggunakan kurikulum Cambridge. Terdapat 29 siswa kelas 3 Sekolah Menengah Pertama yang berpartisipasi dalam penelitian ini. Kreativitas diukur pada empat aspek yaitu kefasihan, fleksibilitas, orisinalitas, dan elaborasi. Hasil penelitian menunjukkan bahwa kreativitas siswa masih berada pada tingkat sedang yang artinya kualitas sudah cukup baik. Sedangkan hasil belajar penguasaan konsep siswa yang diukur dengan tes kognitif menunjukkan peningkatan dengan N-gain 0,42 dan dikategorikan dalam peningkatan sedang. Nilai signifikansi pada uji hipotesis menunjukkan kurang dari 0,05. Hal ini menunjukkan bahwa terdapat perbedaan yang signifikan pada penguasaan konsep siswa dalam mempelajari pengaruh manusia terhadap ekosistem dengan menggunakan Draw IO sebagai mind map digital. Berdasarkan hasil tersebut, Draw IO dapat digunakan sebagai sarana pembelajaran untuk meningkatkan penguasaan konsep dan kreativitas siswa. Keyword: Draw.IO sebagai Digital Mind map, Pemahaman Konsep Siswa, Kreativitas Siswa, dan Pengaruh Manusia terhadap Ekosistem